Lithium secondary battery containing gel polymer electrolyte

By using multifunctional polymer electrolyte without ether groups and lithium cobalt oxide positive electrode materials in lithium-ion batteries, the safety and life problems of lithium-ion batteries under abnormal conditions are solved, and stable operation and long life characteristics are achieved under high voltage.

JP2025504451AActive Publication Date: 2025-02-12SAMSUNG SDI CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024542426
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-18
Filing Date
2022-12-09
Publication Date
2025-02-12
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are prone to explosion or combustion under abnormal conditions, and the resistance increases and capacity decreases when using semi-solid or solid electrolytes, affecting safety and life.

Method used

Using a multifunctional polymer electrolyte without ether groups, a gel polymer electrolyte is formed by injecting and curing into the battery case, and combining lithium cobalt oxide positive electrode material to ensure stable operation at high voltage.

Benefits of technology

It improves the safety and lifespan characteristics of lithium-ion batteries, while maintaining stable driving capabilities at high voltages, avoiding electrolyte decomposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504451000001_ABST
    Figure 2025504451000001_ABST
Patent Text Reader

Abstract

A lithium secondary battery including a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and a gel polymer electrolyte, the positive electrode including a positive electrode active material containing a lithium cobalt-based oxide, the gel polymer electrolyte including a polymer and an electrolyte solution, the polymer having three or more functional groups and not including an ether group, the electrolyte solution including a lithium salt and a solvent, and the lithium salt including lithium difluoro(oxalato)borate and LiBF 4 The present invention relates to a lithium secondary battery comprising:
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium secondary battery containing a gel polymer electrolyte. [Background technology]

[0002] Lithium secondary batteries are widely used not only as portable power sources for mobile phones, notebook computers, digital cameras, etc., but also as medium- to large-sized power sources for power tools, electric bicycles, electric vehicles, hybrid electric vehicles, etc.

[0003] However, general lithium secondary batteries manufactured by injecting liquid electrolytes have safety problems such as explosion or fire when placed under abnormal conditions such as penetration, impact, or pressure, or when overheated. Therefore, attempts have been made to use semi-solid electrolytes or solid electrolytes instead of liquid electrolytes to ensure safety. Among them, gel polymer electrolytes (GPEs) are electrolytes that exhibit a gel-like semi-solid state by including a liquid electrolyte in a polymer solid electrolyte, and can be manufactured in the form of a free standing film and inserted into a battery case, or can be manufactured by injecting the GPE in liquid form into a battery case and then curing it to become a gel-like electrolyte. Gel polymer electrolytes have the advantage of being significantly safer than liquid electrolytes, but have problems with increased resistance and reduced capacity compared to liquid electrolytes. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a lithium secondary battery that can use existing processes without any change by applying a gel polymer electrolyte that can be injected into a battery case without any decrease in viscosity, and that has significantly improved safety and improved life characteristics.The present invention also provides a lithium secondary battery that can be stably driven at high voltages without any electrolyte decomposition phenomenon by applying a positive electrode active material containing a lithium cobalt-based oxide. [Means for solving the problem]

[0005] In one embodiment of the present invention, there is provided a lithium secondary battery comprising a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and a gel polymer electrolyte, wherein the positive electrode comprises a positive electrode active material containing a lithium cobalt-based oxide, the gel polymer electrolyte comprises a polymer and an electrolyte solution, the polymer has three or more functional groups and does not contain an ether group, the electrolyte solution comprises a lithium salt and a solvent, and the lithium salt comprises lithium difluoro(oxalato)borate and LiBF4. Effect of the Invention

[0006] The lithium secondary battery according to the embodiment of the present invention includes a gel polymer electrolyte, which significantly improves safety and life characteristics. The gel polymer electrolyte has an advantage that it can be applied to existing processes since it can be injected into a battery case without a decrease in viscosity, and even if lithium cobalt oxide is used as a positive electrode active material, there is no problem of chemical reaction or decomposition at high voltage, so that the battery can be operated stably. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a cross-sectional view illustrating a lithium secondary battery. [Diagram 2] 1 is a 1H NMR analysis graph for the gel polymer electrolyte prepared in Example 1. [Diagram 3] 1 is a graph showing the life characteristics of the batteries of Example 1 and Comparative Example 1. [Figure 4] 1 is a graph showing the life characteristics of the batteries of Example 1, Example 2, and Comparative Example 2. [Diagram 5] 1 is a graph showing the life characteristics of the batteries of Example 1, Comparative Example 3, and Comparative Example 4. [Figure 6] 1 is a graph showing the life characteristics of the batteries of Examples 1, 3, and 4. [Figure 7] 1 is a graph showing the viscosity of gel polymer electrolyte compositions as a function of polymer content. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention is not limited to the embodiments described herein, but may be embodied in various different forms.

[0009] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.

[0010] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.

[0011] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.

[0012] The drawings have been exaggerated in thickness to clearly depict the various layers and regions, and similar parts are designated by the same reference numerals throughout the specification. When a part, such as a layer, film, region, plate, etc., is said to be "on" or "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.

[0013] Further, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.

[0014] In addition, the average particle diameter and the average size can be measured by methods well known to those skilled in the art, for example, by using a particle size analyzer or by using a transmission electron microscope or a scanning electron microscope. As another method, the size can be measured using a dynamic light scattering method, and the number of particles in each particle size range can be counted by performing data analysis, and the average particle diameter can be calculated from the data. Unless otherwise defined, the average particle diameter is measured using a particle size analyzer and is the diameter (D) of particles whose cumulative volume is 50% by volume in the particle size distribution. 50 ) can mean

[0015] Lithium secondary battery In one embodiment, a lithium secondary battery is provided, which includes a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and a gel polymer electrolyte. FIG. 1 is a schematic diagram showing a lithium secondary battery according to one embodiment. Referring to FIG. 1, a lithium secondary battery 100 includes a battery cell including a positive electrode 114, a negative electrode 112 facing the positive electrode 114, a separator 113 disposed between the positive electrode 114 and the negative electrode 112, and a gel polymer electrolyte (not shown) impregnating the positive electrode 114, the negative electrode 112, and the separator 113, a battery container 120 that contains the battery cell, and a sealing member 140 that seals the battery container 120.

[0016] Gel Polymer Electrolyte A gel polymer electrolyte according to one embodiment includes a polymer and an electrolyte solution, the polymer having three or more functional groups and not containing an ether group, the electrolyte solution including a lithium salt and a solvent, and the lithium salt including lithium difluoro(oxalato)borate and LiBF4.

[0017] The gel polymer electrolyte is prepared by injecting the gel polymer electrolyte into a battery case in which an electrode assembly is inserted and then curing the gel polymer electrolyte, which is advantageous in that it can be applied to the manufacturing process of existing non-aqueous electrolyte batteries. In addition, the gel polymer electrolyte maintains low viscosity when injected into a battery case, thereby maintaining good processability. The gel polymer electrolyte is easily cured by thermal curing or photocuring, and thus can exhibit a gel-like solid state. In a lithium secondary battery, the gel polymer electrolyte can be expressed as containing a crosslinked polymer or a cured polymer and an electrolyte.

[0018] The polymer contained in the gel polymer electrolyte has three or more functional groups, which is advantageous for crosslinking and curing in the battery case, and can exhibit better life characteristics than a battery using a polymer having two or less functional groups. The polymer can also be called a multifunctional polymer that does not contain an ether group. When lithium cobalt oxide is used as the positive electrode active material, the ether group in the electrolyte may undergo a chemical reaction and decompose at a high voltage of about 4.4 V. On the other hand, the polymer in the gel polymer electrolyte according to an embodiment is a multifunctional polymer that does not contain an ether group, and even if lithium cobalt oxide is used as the positive electrode active material, it does not decompose or undergo a chemical reaction, allowing the lithium secondary battery to operate stably for a long period of time. The lithium secondary battery according to an embodiment can achieve better life characteristics than a battery using a gel polymer electrolyte containing an ether-based multifunctional polymer.

[0019] The functional group in the polymer may be, for example, an ester group (-C(=O)O-), a carbonate group (-OC(=O)O-), or a combination thereof. Thus, the polymer may be referred to as an ester-based multifunctional polymer or a carbonate-based multifunctional polymer. The gel polymer electrolyte includes a polymer containing three or more functional groups selected from ester groups and carbonate groups and containing no ether groups, thereby improving processability, ensuring the safety of the lithium secondary battery, and drastically improving the life characteristics.

[0020] The polymer may be derived from a compound containing three or more carbon-carbon double bonds. In other words, the polymer may be understood as a polymerized, crosslinked, or cured compound containing three or more carbon-carbon double bonds. The compound containing three or more carbon-carbon double bonds may be, for example, a compound containing three or more acrylic groups (CH2=CH-C(=O)O-). The carbon-carbon double bonds in the polymer are involved in reactions such as polymerization and crosslinking during the process in which the gel polymer electrolyte hardens in the battery case, and may not be detected in the final battery. In the hardened gel polymer electrolyte state, they can be detected as ester groups or carbonate groups.

[0021] The polymer can be derived from, for example, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, or combinations thereof.

[0022] The polymer may be contained in an amount of 1 to 10% by weight, for example, 2 to 8%, 2 to 6%, or 3 to 5% by weight, based on 100% by weight of the gel polymer electrolyte. When such a content range is satisfied, a gel-like polymer electrolyte can be effectively produced, and the life characteristics of a lithium secondary battery can be improved.

[0023] In the gel polymer electrolyte, the weight ratio of the polymer to the electrolyte solution is 1:99 to 10:90, and may be, for example, 2:98 to 8:92, 2:98 to 6:94, or 3:97 to 5:95. When such a weight ratio is satisfied, a gel polymer electrolyte can be effectively produced, and the life characteristics of a lithium secondary battery can be improved.

[0024] In the gel polymer electrolyte, the electrolyte solution includes a lithium salt and a solvent. The lithium salt includes lithium difluoro(oxalato)borate (LiDFOB) and lithium tetrafluoroborate (LiBF4). The gel polymer electrolyte includes the two types of lithium salts in the electrolyte solution, and thus the life characteristics can be significantly improved. The gel polymer electrolyte according to one embodiment can achieve better life characteristics than a case where the gel polymer electrolyte does not include any one of the two types of lithium salts.

[0025] The LiDFOB and LiBF4 in the electrolyte may be contained in a molar ratio of 20:80 to 80:20, for example, 30:70 to 70:30, or 40:60 to 60:40. By containing the lithium salt in such a molar ratio, the life characteristics of the lithium secondary battery can be improved.

[0026] The electrolyte may further include other lithium salts in addition to LiDFOB and LiBF4. The other lithium salts may be, for example, LiPF6, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, lithium bisfluorosulfonylimide (LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, lithium difluorobisoxalate phosphate, LiCl, LiI, lithium bis(oxalate)borate (LiBOB), or combinations thereof.

[0027] The concentration of the lithium salt in the electrolyte solution is 0.3 M to 4 M, and may be, for example, 0.6 M to 3 M, 0.8 M to 2.5 M, or 1.0 M to 2.0 M. When the concentration of the lithium salt satisfies such a range, the gel polymer electrolyte can exhibit excellent lithium conductivity, can maintain an appropriate concentration when injected into a battery case, and can effectively maintain a gel state after curing.

[0028] The solvent in the electrolyte may be a solvent used in a general non-aqueous electrolyte, and may be, for example, a carbonate-based solvent, an ester-based solvent, or a combination thereof. The solvent may not include an ether-based solvent. When a lithium cobalt-based oxide is used as a positive electrode active material, a problem may occur in which an ether-based component in the electrolyte is decomposed in a high voltage range, and therefore, the electrolyte of the gel polymer electrolyte according to an embodiment may be designed not to include an ether-based solvent.

[0029] The carbonate solvent may be dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), or a combination thereof.

[0030] The ester solvent may be methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, or a combination thereof.

[0031] When two or more kinds of solvents are mixed and used for the electrolyte solution, the mixing ratio can be appropriately adjusted according to the desired battery performance. For example, a mixture of a cyclic carbonate and a chain carbonate can be used as the carbonate-based solvent, and in this case, the cyclic carbonate and the chain carbonate can be mixed at a volume ratio of about 1:1 to about 1:9.

[0032] Meanwhile, the solvent of the electrolytic solution may contain fluoroethylene carbonate. In this case, the gel polymer electrolyte can achieve excellent life characteristics while maintaining good processability. In this case, the fluoroethylene carbonate may be contained in an amount of 5% by volume to 50% by volume with respect to 100% by volume of the solvent, for example, 5% by volume to 40% by volume, 10% by volume to 50% by volume, 15% by volume to 50% by volume, or 20% by volume to 40% by volume. By being contained in the above range, the life characteristics of a lithium secondary battery containing the gel polymer electrolyte can be improved.

[0033] The solvent of the electrolyte may further include an ethylene carbonate-based compound other than fluoroethylene carbonate, or may further include an aromatic hydrocarbon-based organic solvent.

[0034] The ethylenic carbonate compound can be, for example, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, or a combination thereof.

[0035] Examples of the aromatic hydrocarbon solvent include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluol, and the like. The toluene may be toluene, fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene, or combinations thereof.

[0036] positive electrode The positive electrode 114 includes a current collector and a positive electrode active material layer disposed on the current collector, the positive electrode active material layer including a positive electrode active material, and optionally including a binder and / or a conductive material, where the current collector may be, for example, but is not limited to, an aluminum foil.

[0037] The positive electrode active material according to an embodiment includes a lithium cobalt-based oxide. The lithium cobalt-based oxide means an oxide containing lithium and cobalt, and optionally further containing other elements. The lithium cobalt-based oxide can achieve high capacity while exhibiting excellent efficiency and life characteristics, and is economical. The lithium cobalt-based oxide can maintain structural stability without chemically reacting with the gel polymer electrolyte, decomposing or deteriorating during battery operation or under abnormal conditions. When the gel polymer electrolyte according to an embodiment is applied while the lithium cobalt-based oxide is applied as the positive electrode active material, battery performance such as life characteristics can be maximized.

[0038] The lithium cobalt-based oxide may be represented, for example, by the following formula 1: [Chemical formula 1] Li a Co x M 1 y M 2 1-x-y O2

[0039] In the above formula 1, 0.9≦a≦1.8, 0.7≦x≦1, 0≦y≦0.3, M 1 and M. 2 are each independently Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or combinations thereof.

[0040] In the above Chemical Formula 1, 0.8≦x≦1, 0≦y≦0.2, 0.9≦x≦1, 0≦y≦0.1, 0.92≦x≦1, 0≦y≦0.08, or 0.95≦x≦1, 0≦y≦0.05.

[0041] The positive electrode active material may further include a coating layer located on the surface of the lithium cobalt-based oxide. The coating layer may include at least one coating element compound selected from oxides of coating elements, hydroxides of coating elements, oxyhydroxides of coating elements, oxycarbonates of coating elements, and hydroxycarbonates of coating elements. The compound forming the coating layer may be amorphous or crystalline. Examples of the coating elements included in the coating layer include Al, As, B, Ca, Co, Ga, Ge, K, Mg, Na, Si, Sn, Ti, V, Zr, or combinations thereof. The compound forming the coating layer may be, for example, a lithium-metal oxide, a lithium-metal hydroxide, and / or a lithium-metal carbonate. As an example, the coating layer may include lithium zirconium oxide. The coating layer forming process may be a method that does not adversely affect the physical properties of the positive electrode active material, such as spray coating, immersion, dry coating, atomic deposition, evaporation, etc.

[0042] The average particle size (D50) of the positive electrode active material is 1 μm to 25 μm, for example, 4 μm to 25 μm, 5 μm to 20 μm, 8 μm to 20 μm, or 10 μm to 18 μm. The positive electrode active material having such a particle size range can be mixed harmoniously with other components in the positive electrode active material layer, and can achieve high capacity and high energy density. The average particle size is measured by a particle size analyzer, and means the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution.

[0043] The positive electrode active material may be in the form of secondary particles formed by agglomeration of a plurality of primary particles, or in the form of a single crystal, and may be in the form of a sphere or a shape close to a sphere, or may be in the form of a polyhedron or an irregular shape.

[0044] The positive electrode active material may be included in an amount of 55 wt% to 99.8 wt%, for example, 80 wt% to 90 wt%, based on the total weight of the positive electrode active material layer. When included in the above range, the capacity of the lithium secondary battery can be maximized while improving the life characteristics.

[0045] The binder serves to adhere the positive electrode active material particles to each other and to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylate styrene-butadiene rubber, epoxy resin, nylon, etc.

[0046] The content of the binder in the positive electrode active material layer may be about 0.1% by weight to about 5% by weight based on the total weight of the positive electrode active material layer.

[0047] The conductive material is used to impart conductivity to the electrode, and may be any material that does not cause a chemical change in the battery and is electronically conductive, and examples of such materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber containing copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or conductive materials containing mixtures thereof. The content of the conductive material in the positive electrode active material layer may be 0.1% by weight to 5% by weight based on the total weight of the positive electrode active material layer.

[0048] negative electrode In a lithium secondary battery, the negative electrode 112 includes a current collector and a negative electrode active material layer located on the current collector. The negative electrode active material layer includes a negative electrode active material, and may further include a binder and / or a conductive material.

[0049] The negative electrode active material includes a material capable of reversibly inserting / desorbing lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, or a transition metal oxide.

[0050] The material capable of reversibly inserting / extracting lithium ions is a carbon-based negative electrode active material, and may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, and calcined coke.

[0051] As the lithium metal alloy, an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.

[0052] As the substance capable of doping and undoping lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. As the Si-based negative electrode active material, silicon, a silicon-carbon composite, SiOx (0 < x < 2), an Si-Q alloy (where Q is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, excluding Si), as the Sn-based negative electrode active material, Sn, SnO2, an Sn-R alloy (where R is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, excluding Sn), etc. can be mentioned, and at least one of these can also be used in mixture with SiO2. As the elements Q and R, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and those selected from the group consisting of combinations thereof can be used.

[0053] The silicon-carbon composite may be, for example, a silicon-carbon composite including a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon precursor may be coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based medium oil, or polymer resin such as phenol resin, furan resin, or polyimide resin. In this case, the content of silicon may be 10 wt% to 50 wt% based on the total weight of the silicon-carbon composite. The content of the crystalline carbon may be 10 wt% to 70 wt% based on the total weight of the silicon-carbon composite, and the content of the amorphous carbon may be 20 wt% to 40 wt% based on the total weight of the silicon-carbon composite. The thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle size (D50) of the silicon particles may be 10 nm to 20 μm. The silicon particles may have an average particle size (D50) of preferably 10 nm to 200 nm. The silicon particles are present in an oxidized form, and at this time, the atomic content ratio of Si:O in the silicon particles, which indicates the degree of oxidation, may be 99:1 to 33:67. The silicon particles may have a SiO x particles, and SiO x In the formula, x can range from greater than 0 to less than 2.

[0054] The Si-based or Sn-based negative electrode active material may be mixed with a carbon-based negative electrode active material. When the Si-based or Sn-based negative electrode active material is mixed with the carbon-based negative electrode active material, the mixing ratio by weight may be 1:99 to 90:10.

[0055] The content of the negative electrode active material in the negative electrode active material layer may be 95% by weight to 99% by weight based on the total weight of the negative electrode active material layer.

[0056] In one embodiment, the negative electrode active material layer may further include a binder, and may optionally further include a conductive material. The content of the binder in the negative electrode active material layer may be 0.1 wt% to 5 wt% based on the total weight of the negative electrode active material layer. When the negative electrode active material layer further includes a conductive material, the negative electrode active material layer may include 90 wt% to 99.8 wt% of the negative electrode active material, 0.1 wt% to 5 wt% of the binder, and 0.1 wt% to 5 wt% of the conductive material.

[0057] The binder serves to adhere the negative active material particles to each other and to the current collector. The binder may be a water-insoluble binder, a water-soluble binder, or a combination thereof.

[0058] Examples of the non-water-soluble binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, ethylene propylene copolymers, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or combinations thereof.

[0059] The water-soluble binder may be a rubber-based binder or a polymeric resin binder. The rubber-based binder may be selected from styrene-butadiene rubber, acrylate styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and combinations thereof. The polymeric resin binder may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0060] When a water-soluble binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used. The amount of such a thickener used may be 0.1 to 3 parts by weight based on 100 parts by weight of the negative electrode active material.

[0061] The conductive material is used to impart conductivity to the electrodes, and may be any material that does not cause a chemical change in the battery and is electronically conductive. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; metal-based materials in the form of metal powder or metal fiber, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials including mixtures thereof.

[0062] The negative electrode current collector may be selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0063] Separator The separator 113 separates the positive electrode 114 and the negative electrode 112 and provides a path for lithium ions to move, and may be any material that is generally used in lithium ion batteries. In other words, a material that has low resistance to the movement of electrolyte ions and has excellent electrolyte humidification ability may be used. For example, the separator may be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene, or a combination thereof, and may be in the form of a nonwoven fabric or a woven fabric. For example, polyolefin polymer separators such as polyethylene and polypropylene are mainly used in lithium ion batteries, and coated separators containing ceramic components or polymer materials to ensure heat resistance or mechanical strength may also be used, and may be selectively used in a single-layer or multi-layer structure.

[0064] Meanwhile, in one embodiment, a method for producing a lithium secondary battery is provided, the method including: preparing a polymer precursor having three or more functional groups containing a carbon-carbon double bond and not containing an ether group; preparing an electrolyte solution containing a lithium salt containing lithium difluoro(oxalato)borate and LiBF4 and a solvent; mixing the polymer precursor and the electrolyte solution to prepare a gel polymer electrolyte composition; inserting an electrode assembly including a positive electrode containing a positive electrode active material containing a lithium cobalt-based oxide, a separator, and a negative electrode into a battery case; injecting the gel polymer electrolyte composition into the battery case; and curing the gel polymer electrolyte composition to obtain a lithium secondary battery including a gel polymer electrolyte.

[0065] The respective components are as described above. The gel polymer electrolyte composition may be cured by, for example, heat curing, and the heat curing may be carried out at, for example, 50° C. to 200° C. for 10 minutes to 5 hours.

[0066] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.

[0067] Example 1 1. Preparation of gel polymer electrolyte composition Trimethylolpropane trimethacrylate (TMPTMA) was prepared as a polymer precursor. As electrolyte components, lithium difluoro(oxalate)borate (LiDFOB) and LiBF4 were dissolved in a solvent of fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) mixed in a volume ratio of 1:2 to prepare an electrolyte (total 1.2 M) with a molar concentration of 0.6 M each.

[0068] The prepared electrolyte solution and polymer precursor were mixed in a weight ratio of 97:3 to prepare a gel polymer electrolyte composition.

[0069] 2. Battery manufacturing Li 1.02 Co 0.9823 Al 0.0127 Mg 0.005 A positive electrode active material layer composition was prepared by mixing 96 wt% O2 positive electrode active material, 2 wt% polyvinylidene fluoride binder, 2 wt% carbon nanotube conductive material, and N-methylpyrrolidone solvent in a mixer. This was coated on aluminum foil, and then dried and rolled to prepare a positive electrode.

[0070] An electrode assembly was prepared by placing a polyethylene polypropylene multilayer separator between the prepared positive electrode and lithium metal counter electrode. The electrode assembly was inserted into a pouch-type battery case, and the prepared gel polymer electrolyte composition was injected into the case. The electrolyte composition was then hardened by heat treatment at 70° C. for 3 hours to prepare a half cell in which a gel polymer electrolyte was formed.

[0071] Evaluation example 1: 1 H NMR characterization For the gel polymer electrolyte after hardening in Example 1 1A H NMR analysis was performed, and the results are shown in Figure 2. Referring to Figure 2, it was confirmed that the carbon-carbon double bond peak, which is the part indicated by the dotted circle, disappeared. This indicates that all of the carbon-carbon double bonds in the polymer precursor were involved in the reaction during the curing process. In other words, it was found that the polymer precursor of the electrolyte composition was 100% converted into a type of cross-linked polymer.

[0072] Comparative Example 1 (Ether Polymer) A gel polymer electrolyte composition and a battery were prepared in the same manner as in Example 1, except that ethoxylated trimethylolpropane triacrylate (ETPTA), a trifunctional compound containing an ether group, was used as the polymer precursor of the gel polymer electrolyte composition.

[0073] Evaluation example 2: Life characteristics evaluation The batteries manufactured in Example 1 and Comparative Example 1 were initially charged and discharged at a constant current of 0.1 C at 25° C. up to an upper limit voltage of 4.25 V, and then discharged at a constant current of 0.1 C up to a discharge cut-off voltage of 3.5 V. Then, charging and discharging at 0.5 C in the voltage range of 3.5 V to 4.25 V was repeated 200 times. The discharge capacity was measured during the 200 cycles, and the capacity retention rate, which is the ratio of the discharge capacity of each cycle to the initial discharge capacity, was evaluated, and the results are shown in FIG. 3.

[0074] Referring to FIG. 3, in the case of Comparative Example 1 in which an ether-based polymer was used, the capacity retention rate decreased from the beginning of the cycles and reached a retention rate of about 70% at 200 cycles, whereas in the case of Example 1, the capacity retention rate reached a level of 90% at 200 cycles, demonstrating excellent life characteristics.

[0075] Example 2 (polymer change) A gel polymer electrolyte composition and a battery were prepared in the same manner as in Example 1, except that a tetrafunctional compound, pentaerythritol tetraacrylate (PETTA), was used as the polymer precursor of the gel polymer electrolyte composition, and the electrolyte and the polymer composition were mixed in a weight ratio of 98:2.

[0076] Comparative example 2 (bifunctional polymer) A gel polymer electrolyte composition and a battery were produced in the same manner as in Example 1, except that a bifunctional compound, polycaprolactone diacrylate, was used as the polymer precursor of the gel polymer electrolyte composition, and the electrolyte solution and the polymer composition were mixed in a ratio of 96:4 by weight.

[0077] Evaluation example 3: Life characteristic evaluation The batteries prepared in Example 1, Example 2, and Comparative Example 2 were subjected to initial charge / discharge and cycling in the same manner as in Evaluation Example 2. The discharge capacity was measured for 200 cycles, and the capacity retention rate, which is the ratio of the discharge capacity in each cycle to the initial discharge capacity, was evaluated. The results are shown in FIG.

[0078] 4, in the case of Comparative Example 2, the capacity started to decrease from about 50 cycles, and the capacity retention rate at 200 cycles was very low at about 50%, whereas good capacity retention rates were exhibited in the cases of Examples 1 and 2. This confirmed that, compared to Comparative Example 2 in which a bifunctional polymer was applied to the gel polymer electrolyte, Examples 1 and 2 in which a trifunctional or higher polymer was applied had an effect of improving the life characteristics.

[0079] Comparative Example 3 (Change in electrolyte) A gel polymer electrolyte composition and a battery were prepared in the same manner as in Example 1, except that an electrolyte solution was used in which 5 parts by volume of fluoroethylene carbonate and 3 parts by volume of vinylene carbonate were added to 100 parts by volume of a solvent in which ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate were mixed in a volume ratio of 3:5:2, and an electrolyte solution in which LiPF6 lithium salt was dissolved in a molar concentration of 1.15M was used as an electrolyte solution component of the gel polymer electrolyte composition.

[0080] Comparative Example 4 (Change in electrolyte) A gel polymer electrolyte composition and a battery were prepared in the same manner as in Example 1, except that an electrolyte solution was used in which LiTFSI lithium salt was dissolved at a molar concentration of 0.8 M and LiDFOB lithium salt was dissolved at a molar concentration of 0.2 M in a solvent in which ethyl methyl carbonate and fluoroethylene carbonate were mixed in a volume ratio of 3:1 to prepare the gel polymer electrolyte composition.

[0081] Evaluation example 4: Life characteristic evaluation The batteries prepared in Example 1, Comparative Example 3, and Comparative Example 4 were subjected to initial charge / discharge and cycling in the same manner as in Evaluation Example 2. After approximately 80 cycles, the ratio of the discharge capacity in each cycle to the initial discharge capacity was evaluated as the capacity retention rate, and the results are shown in FIG.

[0082] Referring to FIG. 5, Example 1 exhibited a capacity retention rate of 90% or more, indicating excellent life characteristics, whereas Comparative Example 3, in which the electrolyte composition was changed, exhibited a sudden drop in capacity at 20 cycles, and Comparative Example 4, in which a different electrolyte composition was used, exhibited a sudden drop in capacity before the 10th cycle, indicating significantly poor life characteristics, and thus demonstrating that these are not suitable for a gel polymer electrolyte component.

[0083] Example 3 (changing polymer content ratio) A gel polymer electrolyte composition and a battery were prepared in the same manner as in Example 1, except that the electrolytic solution and the polymer precursor were mixed in a weight ratio of 99:1.

[0084] Example 4 (changing polymer content ratio) A gel polymer electrolyte composition and a battery were prepared in the same manner as in Example 1, except that the electrolytic solution and the polymer precursor were mixed in a weight ratio of 95:5.

[0085] Evaluation example 5: Life characteristic evaluation The batteries produced in Examples 1, 3, and 4 were subjected to initial charge / discharge and cycling in the same manner as in Evaluation Example 2. After about 120 cycles, the ratio of the discharge capacity in each cycle to the initial discharge capacity was evaluated as the capacity retention rate, and the results are shown in FIG.

[0086] Referring to FIG. 6, in the case of Example 3 in which the polymer content was 1 wt %, a capacity retention rate of 80% was observed after 120 cycles, while in the cases of Example 1 in which the polymer content was 3 wt % and Example 4 in which the polymer content was 5 wt %, a capacity retention rate of 90% was observed, demonstrating that the battery had a higher level of life characteristics than the other comparative examples.

[0087] Evaluation Example 6: Viscosity evaluation of gel polymer composition The viscosity of the gel polymer electrolyte solution composition before injection into the battery case was measured for each of Example 3 in which the polymer precursor content was 1 wt %, Example 1 in which the polymer precursor content was 3 wt %, Example 4 in which the polymer precursor content was 5 wt %, and Reference Example 1 in which only the electrolyte solution was used without the polymer, and the results are shown in FIG. 7.

[0088] The viscosity was measured using a Brookfield viscometer with a 62 spindle at 5 rpm, and the reference solvent for the viscosity measurement was mineral oil (KS1000 & 5000) as a standard solution for calibrating the viscometer.

[0089] 7, it was confirmed that the conductivity of the gel polymer electrolyte composition decreased as the polymer content increased from 0% to 5%. If the viscosity of the gel polymer electrolyte composition is high relative to the electrolyte due to the polymer component, it may be difficult to inject the electrolyte into a battery case, which may cause problems in processability. However, the gel polymer electrolyte composition according to an embodiment has a lower viscosity than the electrolyte (0% polymer) contained therein, so that good processability can be ensured without any problems during the injection process, and there is an advantage that the manufacturing process of existing non-aqueous electrolyte batteries can be applied as is.

[0090] Although the preferred embodiment has been described in detail above, the scope of the present invention is not limited thereto. In addition, various modifications and improvements made by those skilled in the art using the basic concept defined in the claims also fall within the scope of the present invention. [Explanation of symbols]

[0091] 100: Lithium secondary battery 112: Negative electrode 113: Separator 114: Positive electrode 120:Battery container 140: Encapsulating material

Claims

1. A lithium secondary battery comprising a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and a gel polymer electrolyte, The positive electrode includes a positive electrode active material containing a lithium-cobalt-based oxide, The gel polymer electrolyte includes a polymer and an electrolyte solution, The polymer has three or more functional groups and does not contain an ether group; The electrolyte includes a lithium salt and a solvent, and the lithium salt is lithium difluoro(oxalato)borate and LiBF 4 A lithium secondary battery comprising:

2. 2. The lithium secondary battery according to claim 1, wherein in the polymer of the gel polymer electrolyte, the functional group is an ester group, a carbonate group, or a combination thereof.

3. 2. The lithium secondary battery of claim 1, wherein the polymer in the gel polymer electrolyte is derived from trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, or a combination thereof.

4. 2. The lithium secondary battery according to claim 1, wherein a weight ratio of the polymer and the electrolytic solution in the gel polymer electrolyte is 1:99 to 10:

90.

5. 2. The lithium secondary battery according to claim 1, wherein the concentration of the lithium salt in the electrolytic solution of the gel polymer electrolyte is 0.3M to 4M.

6. The lithium difluoro(oxalato)borate and the LiBF in the electrolyte solution of the gel polymer electrolyte 4 2. The lithium secondary battery according to claim 1, wherein the molar ratio of is 20:80 to 80:

20.

7. 2. The lithium secondary battery according to claim 1, wherein the solvent in the electrolytic solution of the gel polymer electrolyte is a carbonate-based solvent, an ester-based solvent, or a combination thereof.

8. 2. The lithium secondary battery according to claim 1, wherein in the electrolytic solution of the gel polymer electrolyte, the solvent includes fluoroethylene carbonate.

9. The lithium secondary battery according to claim 8, wherein the fluoroethylene carbonate is contained in an amount of 5% by volume to 50% by volume with respect to 100% by volume of the solvent.

10. 2. The lithium secondary battery of claim 1, wherein the lithium cobalt-based oxide in the positive electrode is represented by the following chemical formula 1: [Chemical formula 1] Li a Co x M 1 y M 2 1-x-y O 2 In the above formula 1, 0.9≦a≦1.8, 0.7≦x≦1, 0≦y≦0.3, M 1 and M. 2 are each independently Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or a combination thereof.

Citation Information

Patent Citations

  • 3D network quasi-solid electrolyte, preparation method thereof, quasi-solid lithium ion battery and preparation method of quasi-solid lithium ion battery

    CN113788907A

  • Battery

    JP2004311306A

  • Gel electrolyte and method for producing the same, and battery using the gel electrolyte and method for producing the same

    JP2013525958A

  • Nonaqueous secondary battery

    JP2018060689A

  • Dual ion battery

    JP2020187826A